2001
DOI: 10.1177/135910530100600306
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients and their Spouses: Gender and its Effect on Psychological and Social Adjustment

Abstract: The aim of this research was to examine the effects of gender on the social adjustment and psychological distress experienced by cancer patients and their spouses. A total of 87 patients and spouses participated in the study, with the patients undergoing active medical treatment (chemotherapy, radiation or both) and three months post-diagnosis. Three questionnaires were used to collect data: a personal information one; the Brief Symptom Inventory (BSI), in which stress was examined; and the PAIS-SR, in which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…The percentage of spouses that report problems at a clinically increased level varies between 18% and 30% [5,[8][9][10]. Other studies have shown that when a cancer patient reports a high level of distress, his or her spouse is also found to have a high level of distress [3,11,12]. Similarly, when the patient has psycho-logical adjustment problems, the same is true for the spouse [10,12,13].…”
Section: Introductionmentioning
confidence: 82%
“…The percentage of spouses that report problems at a clinically increased level varies between 18% and 30% [5,[8][9][10]. Other studies have shown that when a cancer patient reports a high level of distress, his or her spouse is also found to have a high level of distress [3,11,12]. Similarly, when the patient has psycho-logical adjustment problems, the same is true for the spouse [10,12,13].…”
Section: Introductionmentioning
confidence: 82%
“…We checked the distribution of clinical features among males and females, and found that more males were diagnosed at stages III and IV (48.8% in males vs. 42.6% in females), with B-symptoms (46.7% in males vs. 39.5% in females) and died from HIV/AIDS (2.4% in males vs. 0.1% in females), which may partially explain the gender disparity. In addition, this gender disparity may also suggest different genetic, hormonal, and metabolic influences on treatment response [20][21][22], or different stress that patients bear and release [23]. Another possible explanation is that some etiological risk factors more frequently observed among males may also have a negative effect on their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Para além disso, o stress emocional pode continuar muito tempo após o tratamento do câncer ter terminado (Harden 2005;Northouse, Mood, Templin, Mellon, & George, 2000;Pitceathly & Maguire, 2003). O sofrimento psicossocial pode ser explicado pelo facto do diagnóstico de câncer muitas vezes gerar uma crise nos cônjuges cuidadores (Harden, 2005;Peleg-Oren & Sherer, 2001) por aumentar a necessidade de lidar com o isolamento social, as despesas e as novas responsabilidades interpostas pelo diagnóstico de câncer, e simultaneamente, prestar apoio emocional à família, sem serem capazes de exprimir as suas próprias angústias.…”
Section: Família Doença Oncológica E Desenvolvimento Psicológico Dosunclassified